Transfusion-Associated Circulatory Overload as a Result of Plasma Transfusion to Correct International Normalized Ratio Before an Invasive Procedure: A Case Report. Issue 2 (15th July 2018) - Cahill, Christine M.; Blumberg, Neil; Refaai, Majed A.
Abstract : Plasma transfusion is commonly used to correct elevated international normalized ratio (INR) before invasive procedures. A 54-year-old woman presented to the emergency department with abdominal pain. Workup revealed Streptococcus pneumoniae peritonitis. Her hospitalization was complicated by respiratory failure, fluid overload, atrial fibrillation, and acute kidney injury. Patient underwent 2 paracentesis (9 L removed). Four units of plasma were transfused to correct an INR of 3.0 (goal 1.5) for a transjugular intrahepatic portosystemic shunt procedure. INR remained at 1.9, and she developed acute pulmonary edema and died within 24 hours. Prothrombin complex concentrates may have been a more appropriate treatment option in this case.